PENGEMBANGAN APLIKASI MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN TIK (MICROSOFT EXCEL 2007) DENGAN PENDEKATAN PEMBELAJARAN TUNTAS PADA SISWA KELAS VIII DI SMP N 5 SINGARAJA - Luh Dita Aryastiti (Universitas Pendidikan Ganesha, 2012)
This research was aimed (1) to design and implement the interactive multimedia application of ICT subject (Microsoft Excel 2007) which used Mastery Learning for student of VIII class at SMPN 5 Singaraja. (2) to know the response from student for the interactive multimedia application of ICT lessons (Microsoft Excel 2007). The subject of this research are all students of VIII class at SMPN 5 Singaraja academic year 2012/2013 which are 31 students. This research is research and development (R&D). The data collected include students’ response data towards the development for interactive multimedia application of ICT subject (Microsoft Excel 2007) with the use of Mastery Learning by descriptively. The data of students’ response were analyzed by descriptive. The interactive multimedia was developed by using Macromedia Flash 8 as well as some supporting software such as Adobe Photoshop CS to create and edit images, Adobe Premiere Pro1.5 to process video, and Camtasia Studio 5 for video editing. The results of this research showed that students and teacher response of interactive multimedia application for ICT subject (Microsoft Excel 2007) with the use of Mastery Learning are positive categorized.